Sinergisitas Guru PAI dengan Orang Tua Siswa dalam Penanaman Akhlak di SD Negeri Lebaksari - Duwi Susanti; Mahbub Junaidi; Siti Lathifatus Sun'iyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The cultivation of moral values among elementary school students is a crucial process in shaping religious and ethical character from an early age. Islamic Religious Education (PAI) teachers play a central role in guiding students; however, the success of this process significantly depends on synergy with parents. This study aims to describe the forms of synergy between PAI teachers and parents in instilling moral values at SD Negeri Lebaksari, as well as to identify its supporting and inhibiting factors. This research employed a descriptive qualitative method, using data collection techniques such as observation, interviews, and documentation. The findings reveal that synergy takes place through digital communication, joint religious activities, and the reporting of students' development. Supporting factors include mutual awareness of the importance of moral education and the principal’s support, while the main obstacles are the lack of parental understanding and their busy schedules. This study underscores the importance of active and continuous collaboration between schools and families in nurturing a generation with noble character. Keywords: Elementary School, Moral Cultivation, Synergy of Islamic Religious Education teachers.